Dampak Penerapan Teknologi Artificial Intelligence (AI) terhadap Praktik MSDM - Enny Istanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes in various aspects of life, including in the practice of Human Resource Management (HRM). This study will use a qualitative approach with an explanatory case study design to investigate in depth the impact of the application of AI on Human Resource Management (HRM) practices in various organizations This research reveals that the application of Artificial Intelligence technology has had a significant transformative impact on Human Resource Management practices in organizations. AI-based sentiment analysis has enabled organizations to better understand employee satisfaction and engagement levels, aiding in performance management-related decision-making. Organizations need to develop clear policies and procedures for managing the use of AI, including mechanisms to address potential bias and protect employee privacy. In the context of hiring and selection, AI has substantially improved process efficiency by automating resume screening and performing predictive analytics to identify the most suitable candidates. Nonetheless, the study also identifies several challenges in the application of AI in MSDM. In a broader context, the application of AI in MSDM also has implications for legal and regulatory aspects.